ISOLASI DAN IDENTIFIKASI KOMPONEN KIMIA EKSTRAK N-HEKSAN DAUN PALA (Myristica fragrans) - Virsa Handayani (Fakultas Farmasi UMI, 2014)
Nutmeg plant is a multi-purpose plant because each part can be utilized in the industry. Nutmeg leaves contain essential oils and phenolic compounds. Essential oils are used as traditional medicine ingredients and as raw material for the manufacture of cosmetics, soaps, perfumes and others. This study aimed to isolate and identify the chemical components in the leaves of nutmeg (Myristica fragrans). Have done isolation and Identification of chemical components of the methanol extract of leaves pala (Myristica fragrans.) of 500 grams to determine the class of chemical components caontained in the leaf pala (Myristica fragrans.). The methanol extract which obtained by maseartion method 9,45 grams continued by solid liquid partition with n-hexane 4,61 grams extract. N-hexan extract isolated by column chromatography method obtained 37 bottles vials. Fraction D of the merger based on the appearance of spotting the chromatograms isolated by preparative thin-layer chromatography method, obtained 3 band. D.1 fractions isolated by TLC obtained a stain. In fractions spotting D.1 is obtained by testing a single two-dimentional TLC ang the elution system of multi eluen. Interpretation UV-Visible spectra data showed maximum absorption at a wavelength 0f 273 nm and showed infrared fungtional group (OH) on the wave number (3927.78 cm-1, 3828.59 cm-1, 3743.30 cm-1, 3387.93 cm-1), group (CH) on the wave number (2925.93 cm-1, 2859.02 cm-1, 2364.17 cm-1), alken group (C = C) aromatik on the wave number (1642.54 cm-1, 1565.88 cm-1, 1516.65 cm-1, 1458.92 cm-1, 1114.33 cm-1), benzene group on the wave number ( 698.24 cm-1). Single spots obtained gave a positive reaction to spotting visualizer class of flavonoids. Key words : Nutmeg , Isolation, Essential Oils.